2019
DOI: 10.1111/1440-1681.13166
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of the proliferation and invasion of breast cancer cells by ST7L occurs through inhibition of activation of Wnt/GSK‐3β/β‐catenin signalling

Abstract: Emerging evidence has indicated that suppression of tumorigenicity 7-like (ST7L) is a tumour suppressor in multiple types of cancers. However, the functional involvement of ST7L has not been studied in breast cancer. In the present study, we aimed to investigate the potential biological function of ST7L in breast cancer. Herein, we found that ST7L expression was frequently downregulated in breast cancer cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…So far, no previous studies showed either of these genes to be related to bladder cancer risk. As ST7L is a key factor of Wnt/GSK-3β/β-catenin signaling pathway, 46,47 the interaction with ADSS2 might inhibit the function of ST7L that is the suppression of tumorigenicity, and thereby enhance the development of bladder cancer. Similarly, the LARP4B (10:890252)-LHPP (10:126164319) interaction was also found to increase the bladder cancer risk in both Caucasian and non-Caucasian participants.…”
Section: Discussionmentioning
confidence: 99%
“…So far, no previous studies showed either of these genes to be related to bladder cancer risk. As ST7L is a key factor of Wnt/GSK-3β/β-catenin signaling pathway, 46,47 the interaction with ADSS2 might inhibit the function of ST7L that is the suppression of tumorigenicity, and thereby enhance the development of bladder cancer. Similarly, the LARP4B (10:890252)-LHPP (10:126164319) interaction was also found to increase the bladder cancer risk in both Caucasian and non-Caucasian participants.…”
Section: Discussionmentioning
confidence: 99%
“…It reduces the expression level of β-catenin and GSK-3β phosphorylation, leading to inhibition of β-catenin transcription. Consequently, knockdown of ST7L promotes growth, invasion, and EMT of tumor cells [ 175 ]. There was miR-331-3p up regulations in PC cells and clinical specimens, which was associated with the advanced stage and distant invasion.…”
Section: Wnt Signaling Pathwaymentioning
confidence: 99%
“…Wang et al [ 34 ] first demonstrated that the expression of the suppression of tumorigenicity 7 like ( ST7L ) is downregulated in BC cells, and more importantly, that ST7L acts as an antitumor supervisor by reducing GSK-3β phosphorylation and inducing β-catenin degradation. However, the mechanisms through which ST7L controls GSK-3β phosphorylation are still missing ( Table 1 ).…”
Section: Canonical Wnt Pathway and Bcmentioning
confidence: 99%